2019
DOI: 10.33086/jhs.v12i1.832
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Tingkat Depresi Dengan Kejadian Insomnia Pada Lanjut Usia Di Griya Werdha Jambangan Surabaya

Abstract: Gangguan kesehatan yang dialami oleh lansiaseperti mengalami penurunan untuk berfikir jernih, adanya penurunan kontak sosial yang membuat lansialebih memilih diam dan tidak menceritakan masalah yang dialaminya cenderung dipendam sendiri.Lansia yang mengalami depresi ringan sebanyak 66,0%. Tujuan penelitian ini untuk menganalisis hubungan tingkat depresi dengan kejadian insomnia.Desain penelitian ini adalah analitik dengan cross sectional. Populasi 53 responden dan besar sampel 47 responden.Menggunakan caraprob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…5 Another study showed that the depression rate of the elderly who were treated at the nursing home reached 66%. 6 According to these data, it can conclude that the distribution of depression in this study corresponds to the literature because the rate of depression in the elderly with physical illness and outpatients is relatively more minor than the elderly living in nursing home. This study showed that most participants (89.4%) did not experience depression despite their physical illness and were outpatients.…”
Section: Discussionsupporting
confidence: 81%
“…5 Another study showed that the depression rate of the elderly who were treated at the nursing home reached 66%. 6 According to these data, it can conclude that the distribution of depression in this study corresponds to the literature because the rate of depression in the elderly with physical illness and outpatients is relatively more minor than the elderly living in nursing home. This study showed that most participants (89.4%) did not experience depression despite their physical illness and were outpatients.…”
Section: Discussionsupporting
confidence: 81%
“…Depresi pada lansia memberikan dampak di antaranya memperpendek harapan hidup dengan memperburuk kemunduran fisik pada lansia, menghambat pemenuhan tugas perkembangan lansia, menurunkan kualitas hidup lansia, menguras emosi dan 3 finansial orang yang terkena serta keluarga dan sistem pendukung sosial yang dimilikinya [14]. Konsekuensi yang serius dari depresi pada usia lanjut apabila tidak mendapat perhatian dan penanganan adalah semakin memburuknya penyakit yang sedang diderita, kehilangan harga diri dan keinginan untuk bunuh diri [15]. Depresi merupakan gangguan psikiatri umum pada lansia.…”
Section: Pendahuluanunclassified
“…The changes experienced have an impact on the quality of life and daily activities, resulting in disruption of the social role and causing dependence on others. Most of the older people who live at the Jambangan Nursing Home in Surabaya experience problems such as changes in emotional conditions, irritability, often day dreaming, feeling anxious about the illness, they think about their children and fear of death (Hatmanti, Mawarda & Muzdalifah, 2019). This fact is a sign of the need to increase health services that are more focused on the older people, because with an increase in the number of older people will be at risk of experiencing vulnerability as a group using health services, as a result of various health problems that arise due to decreased physiological and psychological functions.…”
Section: Introductionmentioning
confidence: 99%